2006
DOI: 10.2355/isijinternational.46.241
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Microstructure of Al-Si/SiCp Composites during Stir Casting Process with Particle Pushing Model

Abstract: Particle distribution has vital influence on the microstructure and the final performance of particle reinforced metal matrix composite. The formation of microstructure of SiC particle reinforced Al-7.0mass%Si composite made by stir casting was simulated in this paper. Two-dimensional models under normal solidification condition including macro heat transfer, micro nucleation, equiaxed dendrite growth and particle pushing were presented. Two sets of meshes were used to carry out macro and micro calculation, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This technique can predict the presence of any defects in the casting to screen better casting parameters, improve the casting quality, and realize cost savings. Li et al [6] used a SiC ceramic/Al-Si alloy composite as the research object and simulated the microstructure of the composite made by stir casting. The simulation results showed that particle clustering/ accumulation was caused by particle pushing, and the particles were distributed more uniformly as the pouring temperature increased.…”
Section: Introductionmentioning
confidence: 99%
“…This technique can predict the presence of any defects in the casting to screen better casting parameters, improve the casting quality, and realize cost savings. Li et al [6] used a SiC ceramic/Al-Si alloy composite as the research object and simulated the microstructure of the composite made by stir casting. The simulation results showed that particle clustering/ accumulation was caused by particle pushing, and the particles were distributed more uniformly as the pouring temperature increased.…”
Section: Introductionmentioning
confidence: 99%
“…But it is difficult to measure the velocity distribution of molten aluminum under such a tough environment. Till date, with the help of computational simulation and numerical analysis method, several researchers [ 21–23 ] have paid attention on the quantification of particles clustering in the aluminum matrix composites under different fluid field parameters.…”
Section: Introductionmentioning
confidence: 99%